2020
DOI: 10.1021/acsinfecdis.0c00452
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylenimine: An Intranasal Adjuvant for Liposomal Peptide-Based Subunit Vaccine against Group A Streptococcus

Abstract: Group A Streptococcus (GAS) and GAS-related infections are a worldwide challenge, with no commercial GAS vaccine available. Polyethylenimine (PEI) attaches to the cells surface and delivers cargo into endosomal and cytosolic compartments. We hypothesized that this will confer mucosal adjuvant properties for peptide antigens against group A Streptococcus (GAS). In this study, we successfully demonstrated the development of PEI incorporated liposomes for the delivery of a lipopeptide-based vaccine (LCP-1) agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…In addition, some polymer, such as polyethylenimine (PEI), which could attach to the cells’ surface and deliver cargo into endosomal and cytosolic compartments, was introduced in the lipopeptide-based vaccine design. PEI incorporated in liposome peptide vaccine could induce significant specific mucosal and systemic antibodies, which effectively opsonize multiple isolates of clinically isolated GAS ( 407 ). Further, they found that the ratio of PEI, rather than molecular weight, present in the liposome vaccines impact immune response ( 408 ).…”
Section: Protein-based Bacterial Vaccine Delivery Systemmentioning
confidence: 99%
“…In addition, some polymer, such as polyethylenimine (PEI), which could attach to the cells’ surface and deliver cargo into endosomal and cytosolic compartments, was introduced in the lipopeptide-based vaccine design. PEI incorporated in liposome peptide vaccine could induce significant specific mucosal and systemic antibodies, which effectively opsonize multiple isolates of clinically isolated GAS ( 407 ). Further, they found that the ratio of PEI, rather than molecular weight, present in the liposome vaccines impact immune response ( 408 ).…”
Section: Protein-based Bacterial Vaccine Delivery Systemmentioning
confidence: 99%
“…Furthermore, the use of PEI to control CpG release presents an additional consideration, as PEI has been used as a vaccine adjuvant capable of improving DC antigen presentation, mixed-Th1/Th2 responses, and IgG antibody titers. [18,[47][48][49] PEI has also been shown to stimulate type-2 immunity and secretion of IL-5 and IL-10, among other cytokines. [49][50][51] These reports are broadly consistent with our finding that PLG scaffolds containing GM-CSF, OVA, and PEI alone (without CpG) induced an IL-5, Th2-biased response (Figure 2f,g).…”
Section: Discussionmentioning
confidence: 99%
“…The particle size distribution of the malaria vaccine components was measured using a laser particle analyser (Zeta sizer 2000E, Malvern Instruments Ltd., Malvern, UK). The emulsion was diluted 10 times, then transferred to disposable zeta sizer cuvettes before measurement at 25˚C with a 173˚light scattering angle [27].…”
Section: Particle Size Analysismentioning
confidence: 99%